Alcohol consumption in Spanish mental health patients vs. working population (2018)
Introduction: Alcohol consumption has a high prevalence in society and its chronic consumption is one of the main factors related to health condition in an individual, along with other aspects concerning lifestyle. Regarding the health-disease correlation, it is one of the main determinants of health, from an epidemiological point of view, and has been a traditional object of study from different perspectives and in diverse population groups.Objective: To compare consumption patterns and related variables in two different groups: patients in mental health units and workers in general.Materials and methods: Cross-sectional study in a population of 1 180 service workers and 304 patients in a mental health unit. Sociodemographic and work aspects, as well as pattern of alcohol consumption were analyzed for both populations.Results: Differences in both groups were observed regarding the number of consumers, quantity of consumption and type of beverages consumed, differences that disappear, in part, when comparing groups of workers of both population samples.Conclusions: Differences in the consumption pattern of both populations lead to different preventive-assistance strategies and to the need for implementing coordinated actions by specific programs among those affected.